Approach to the Core Structure of the Polycyclic Alkaloid Palhinine A - Gaugele, Dominik; Maier, Martin E. (Synlett, 2013)
A synthesis of the tricyclic partly substituted core structure of palhinine A was achieved. To reach the bicyclo[2.2.2]octane motif a domino Michael reaction was employed as a key step. After Arndt–Eistert homologation and intramolecular aldol reaction the isotwistane core could be obtained after simple functional-group manipulations.
Keywords: palhinine A; domino Michael reaction; X-ray crystal structure; Arndt–Eistert homologation; intramolecular aldol reaction